Prevalence of sexual dysfunction and urinary incontinence and associated risk factors in Turkish women - Cayan, Selahittin; Yaman, Onder; Orhan, Irfan; Usta, Mustafa; Basar, Murad; Resim, Sefa; Kadioglu, Ates (Elsevier Science Bv, 2016)
Objectives: Female sexual dysfunction (FSD) and urinary incontinence (UI) are associated risk factors that might cause each other. No study has investigated prevalence of FSD and UI in the same population. The aims of the study were to investigate the prevalence of FSD and UI and associated risk factors in the same population. Study design: : The study included 1217 women in 20 provinces, representing the geographical regions of Turkey. Women aged >= 18 years with active sexual life in the last 6 months were enrolled. FSD, overactive bladder, UI, depression, and sexual distress were investigated using validated scales. Risk factors that might predict FSD and UI were determined in the same population. Results: The prevalence of FSD and UI was 52.5% and 14.6%, respectively. Comparing the women with and without FSD, those with FSD were older, had higher body mass index (BMI), less physical exercise, older spouses, lower educational level, and lower rates of smoking and alcohol consumption. The rates of women in menopause and those with a spouse/partner having erection problem and the rates of UI, depression, and sexual distress were higher in the FSD group. Age of spouse, low educational level, not smoking, not consuming alcohol, menopause, not giving consent to spouse/partner to use sexual performance-enhancing drugs when necessary, depression, and sexual distress were the significant risk factors for FSD. Of the women with UI, 56% had overactive bladder symptoms, 32% had stress UI, and 12% had mixed type UI. Comparing the women with and without UI, those with UI were older, had higher BMI, lower educational level, and older spouses. The rate of menopausal women and the rates of FSD, depression, and sexual distress were higher in the UI group. Menopause and FSD were the significant risk factors for UI. Conclusions: This is the first study to investigate prevalence of FSD and UI in the same population. UI deteriorates sexual functions of women. Therefore, both conditions should be assessed when women complain of either sexual or urinary problems. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Sexual dysfunctions; Urinary incontinence; Female; Prevalence